Tgv glass substrate and its deep hole copper plating layer uniformity control electroplating solution and control method

CN122879773APending Publication Date: 2026-10-09ZHEJIANG XINGKE OPTOELECTRONICS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611010141.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0007]本发明的一个目的是提出了一种TGV 深孔铜镀层均匀性调控电镀液,解决了现有技术中的电镀液不能同时满足镀层均匀性与低应力的缺陷

Benefits of technology

本发明的TGV 深孔铜镀层均匀性调控电镀液能够降低镀层内应力,避免镀层脆性增加,稳定镀液性能,为均匀性-应力协同调控电镀液。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a TGV deep hole copper plating layer uniformity regulation electroplating solution, which can realize 100% uniform filling of a TGV deep hole without a cavity and a defect with a deep-diameter ratio of 15:1. The application also provides a TGV deep hole copper plating layer uniformity regulation and stress optimization method, which realizes precise control of the uniformity of a high aspect ratio TGV deep hole copper plating layer and low-level stability of internal stress, greatly improves the uniformity of the plating layer, realizes ultra-low-level stable control of the internal stress, significantly optimizes electrical performance, and reaches high-level packaging standards in long-term reliability, and is excellent in mass production adaptability. The TGV glass substrate provided by the application realizes precise control of the uniformity of a deep hole copper plating layer and low-level stability of internal stress, and can realize large-scale mass production with high consistency, high reliability and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass through-hole (TGV) electroplating technology for advanced semiconductor packaging, and particularly to a method for precise control of uniformity and long-term optimization of internal stress in high aspect ratio TGV deep hole copper plating. This method can be widely applied to chiplet heterogeneous integration, 3D IC stacking, 6G RF device packaging, Mini / Micro LED display driving, high-reliability packaging for automotive electronics, aerospace electronic packaging, and other fields. Background Technology

[0002] As semiconductor packaging technology rapidly iterates towards higher density, thinner profiles, higher frequencies, and higher reliability, advanced packaging architectures such as Chiplet heterogeneous integration and 3D IC stacking place extreme demands on the performance consistency and long-term reliability of vertical interconnect structures. Traditional through-silicon via (TSV) technology is severely limited in its application in high-reliability scenarios such as radio frequency, automotive, and aerospace due to inherent defects such as the high dielectric constant of silicon substrates, high high-frequency losses, and poor matching of the coefficient of thermal expansion (CTE) with organic substrates.

[0003] Through-Glass Via (TGV) technology, using glass as a substrate, possesses core advantages such as low dielectric constant, low dielectric loss, excellent insulation performance, high CTE compatibility with organic substrates, optical transparency, and low cost, making it a core vertical interconnect technology for next-generation advanced packaging. Currently, the depth-to-diameter ratio of TGV technology has rapidly increased from 3:1 to over 10:1, and the requirements for copper plating have upgraded from basic "no void filling" to "controllable uniformity of plating throughout the hole + low and stable internal stress." Plating uniformity directly determines the dispersion of interconnect resistance and the consistency of high-frequency performance, while plating internal stress directly affects the long-term reliability and yield of the packaging structure.

[0004] The current mainstream TGV copper plating process in the industry is PVD seed layer preparation + electroplated copper filling, coupled with conventional DC / pulse reverse electroplating process. This process has inherent defects that cannot be overcome in terms of uniformity and stress control. 1. Poor uniformity of plating in high aspect ratio deep holes, and inability to guarantee consistency: For TGV deep holes with an aspect ratio ≥ 5:1, due to the limiting diffusion effect during the electroplating process, the mass transfer of copper ions and organic additives in the hole is severely unbalanced, resulting in a deposition rate at the hole opening that is much higher than that at the bottom of the hole. It is common in the industry that the thickness difference between the plating at the hole opening and the bottom of the hole is ≥ 5 μm, and the thickness difference is even greater than 10 μm when the aspect ratio is 10:1. The through-hole resistance dispersion coefficient exceeds 15%, which cannot meet the consistency requirements of high-density packaging. Conventional pulse reverse electroplating can only achieve basic void-free filling, and cannot accurately control the mass transfer and deposition process in the deep hole, thus failing to solve the problem of uniformity throughout the hole. 2. Lack of stress control in the coating leads to high risk of reliability failure: Existing TGV copper plating processes generally only focus on the filling effect and ignore stress control throughout the entire process from deposition source to post-processing. Mismatches in plating solution formulation, current parameters, and post-processing processes result in residual tensile stress in the coating generally exceeding 120MPa. In subsequent chemical mechanical polishing (CMP), high-temperature reflow, and temperature cycling processes, coating cracking, interface peeling, and even glass substrate breakage are very likely to occur. As a result, the packaging yield loss caused by this exceeds 20% in the industry, which cannot meet the JEDEC high reliability packaging standards for automotive and aerospace applications. 3. There is an irreconcilable technical contradiction between uniformity and low stress: Existing optimization solutions in the industry generally suffer from the bottleneck of "paying one thing while losing another": improving uniformity with high-concentration leveling agents will lead to increased coating brittleness and soaring internal stress; reducing internal stress by adding organic stress-reducing agents will lead to decreased plating solution stability and decomposition products contaminating the plating solution, which will exacerbate uneven coating deposition; equipment modification solutions such as ultrasonic-assisted and horizontal electroplating are costly to modify and have limited effect on improving mass transfer in deep holes with a mass transfer ratio of 10:1 or higher, and cannot be adapted to large-scale production.

[0005] To address the aforementioned shortcomings, existing optimization technologies in the industry all face insurmountable bottlenecks: while chemical plating as a base layer can improve the uniformity of the conductive layer within the hole, it suffers from weak coating adhesion, high internal stress, and difficulty in wastewater treatment; laser-induced metallization processes can cause thermal damage to the glass substrate, generating microcracks and are unsuitable for deep holes with a ratio greater than 3:1; and plasma injection processes still require vacuum equipment, are costly, and cannot achieve uniform modification within deep holes.

[0006] In summary, existing TGV copper plating technology cannot simultaneously achieve precise control of plating uniformity across the entire deep hole with high aspect ratio and closed-loop optimization of plating internal stress throughout the entire process. The technical contradiction between uniformity and low stress cannot be resolved, becoming the core bottleneck restricting the large-scale commercial application of high-reliability TGV packaging. Summary of the Invention

[0007] One objective of this invention is to provide a TGV deep-hole copper plating solution for uniformity control, which solves the problem that existing plating solutions cannot simultaneously satisfy both plating uniformity and low stress.

[0008] Another objective of this invention is to propose a method for controlling the uniformity of TGV deep-hole copper plating, which solves the common industry problems in existing TGV copper plating technology, such as large thickness differences in deep-hole plating, high resistance dispersion, uncontrolled internal stress, inability to achieve both uniformity and low stress, and insufficient long-term reliability.

[0009] The technical solution of this invention is implemented as follows: This invention discloses a TGV deep-hole copper plating uniformity control electroplating solution, which is a special electroplating solution for uniformity-stress synergistic control. Based on mass-volume concentration (g / L), it comprises the following components: Main salt: Copper sulfate (CuSO4·5H2O) 180-220g / L, providing the Cu required for copper plating. 2+ ; Electrolyte: Sulfuric acid (H2SO4, 98%) 60-80 g / L, to adjust the pH of the plating solution (1.0-1.8) and improve conductivity; Composite complexing agent: disodium ethylenediaminetetraacetate (EDTA-2Na) 8-12g / L, sodium citrate 5-10g / L, which forms a stable complex with copper ions, reduces the concentration difference of copper ions between the orifice and the bottom of the orifice, inhibits rapid deposition at the orifice, and lays the foundation for uniform deposition throughout the orifice. Composite accelerators: disodium bis(3-sulfopropyl) disulfide (SPS) 0.01-0.03 g / L, sodium 3-mercapto-1-propanesulfonate (MPS) 0.005-0.015, preferentially adsorbed on active sites at the bottom of the pore, selectively increasing the copper deposition rate at the bottom of the pore, and precisely reducing the deposition rate difference between the pore opening and the bottom of the pore; Composite leveling agent: 2-mercaptobenzimidazole (MBI) 0.02-0.04 g / L, polyethyleneimine alkyl compound (PN) 0.01-0.03 g / L, preferentially adsorbed in the high current density area of ​​the orifice, inhibiting orifice protrusion deposition, while refining copper grains and reducing the internal stress of the coating; Composite stress reducer: polyethylene glycol (PEG, molecular weight 6000~10000) 0.8-1.2 g / L, modified nano silica 0.2-0.5 g / L, sodium sulfite 0.5-1.0 g / L. PEG forms a smooth adsorption film on the coating surface, stabilizing the deposition process; modified nano silica embeds into the grain boundaries of the coating, inhibiting grain coarsening and reducing internal stress; sodium sulfite removes oxidizing impurities from the plating solution, preventing increased coating brittleness and stabilizing the performance of the plating solution. Solvent: Deionized water, used to dissolve all components and form a homogeneous system.

[0010] A method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating includes the following steps: Step 1, Pretreatment of TGV glass substrate: The glass substrate with prepared through holes is subjected to alkaline degreasing, water washing and BOE buffer micro-roughening in sequence, and then water washing, blowing and vacuum drying. Step 2, Plasma interface activation treatment: The glass substrate treated in Step 1 is activated by oxygen plasma interface. Step 3, silane coupling agent interface modification: The activated TGV glass substrate is immersed in a silane coupling agent treatment solution for modification, and then cleaned, dried and vacuum cured. Step 4, Copper ion pre-adsorption treatment: The modified TGV glass substrate is left to stand in the electroplating solution without electricity. Step 5, Coordinated control of uniformity and stress in multi-segment coupled pulse electroplating: Using the TGV glass substrate obtained in step 4 as the cathode and the phosphorus copper ball as the anode, deep hole copper plating is completed in the electroplating solution using four-segment coupled pulse electroplating. Step 6, gradient annealing: After electroplating, clean and dry, then perform three-stage gradient annealing in a nitrogen atmosphere.

[0011] further, Step 1, Pretreatment of TGV glass substrate: The glass substrate with prepared through holes is subjected to alkaline degreasing at a temperature of 50-60℃ and an ultrasonic time of 10-15 min, followed by rinsing with flowing deionized water for 3-5 min, micro-roughening with BOE buffer etching solution at a temperature of 20-25℃ and an etching time of 30-120 s. The volume ratio of hydrofluoric acid, ammonium fluoride, and water in the BOE buffer etching solution is 1:5:1. The substrate is then rinsed with flowing deionized water for 5-10 min, dried with high-purity nitrogen, and vacuum dried at 100-120℃ for 10-20 min to obtain a clean, micro-roughened TGV glass substrate with excellent interface consistency. Step 2: Place the TGV glass substrate processed in Step 1 into the plasma equipment cavity for oxygen plasma activation: cavity vacuum degree 10~30Pa, oxygen flow rate 20~50sccm, radio frequency power 100~300W, processing time 5~15min; remove immediately after processing and proceed to the next step. Step 3, Silane Coupling Agent Interface Modification: The activated TGV glass substrate is immediately immersed in the silane coupling agent treatment solution at a temperature of 25~40℃ for 30~90 min. After treatment, it is ultrasonically cleaned with anhydrous ethanol for 3~5 min, dried with nitrogen, and vacuum cured at 100~120℃ for 30~60 min. The silane coupling agent treatment solution is a mixture of silane coupling agent, anhydrous ethanol, and deionized water, with a volume ratio of 5:90:5. The silane coupling agent is a mixture of KH-550 (3-aminopropyltriethoxysilane) and KH-590 (3-mercaptopropyltrimethoxysilane), with a mass ratio of 1~3:1. Step 4, copper ion pre-adsorption equalization treatment: Immerse the modified TGV glass substrate in the electroplating solution and let it stand for 10-30 minutes at room temperature without electricity to allow copper ions to fully complex with the amino / thiol active groups on the glass surface, forming a uniformly distributed copper ion adsorption layer on the glass surface and the hole wall, eliminating the difference in nucleation sites between the hole opening and the hole bottom. Step 5, Coordinated control of uniformity and stress in multi-segment coupled pulse electroplating: Using the TGV glass substrate obtained in step 4 as the cathode and the phosphorus-containing copper balls as the anode, with a phosphorus content of 0.03~0.06% by mass, the substrate is placed in the electroplating solution at a temperature of 22~28℃. Circulation filtration and microporous aeration stirring are used, and the cathode oscillation frequency is 5~10 times / min. A four-segment coupled pulse electroplating method is adopted. Step 6, long-term optimization of gradient annealing stress: After electroplating, rinse with flowing deionized water for 10-15 minutes and dry with high-purity nitrogen; place in a nitrogen atmosphere oven and perform three-stage gradient annealing.

[0012] Furthermore, the aperture of the glass substrate with the through-hole is 10~100μm, and the aspect ratio is 2:1~15:1. The specific method of the four-segment coupled pulse electroplating in step five is as follows: Uniform nucleation pre-plating stage: forward pulse current 0.1~0.3A / dm², pulse width 10~20ms, duty cycle 10~20%, time 5~10min; Deep hole mass transfer equalization stage: forward pulse current 0.3~0.8A / dm², width 20~40ms, duty cycle 20~30%; reverse pulse current is 1 / 4~1 / 3 of the forward pulse current, width 1~2ms, duty cycle 1~3%, time 20~40min; Isotropic uniform filling stage: forward pulse current 0.8~2.0A / dm², width 10~30ms, duty cycle 10~25%; reverse pulse current is 1 / 3~1 / 2 of the forward pulse current, width 2~3ms, duty cycle 2~5%; time 60~180min (adjusted synchronously according to depth-to-diameter ratio). Densification stress reduction stage: positive pulse current 0.3~0.5A / dm², width 30~50ms, duty cycle 30~40%, time 5~10min.

[0013] Furthermore, the specific method for three-stage gradient annealing is as follows: First stage: Hold at 120~150℃ for 20~30 minutes to eliminate adsorbed hydrogen and micro-stress in the coating; Second stage: Hold at 180~220℃ for 30~60 minutes to achieve appropriate rearrangement of copper grains, eliminate macroscopic residual internal stress, and avoid excessive grain coarsening. The third stage involves cooling the furnace to room temperature at a rate not exceeding 5°C / min to avoid generating new internal stresses due to thermal stress mismatch during the cooling process.

[0014] Preferably, the temperature for micro-coarsening with BOE buffer etching solution is controlled at 22~25℃, and the etching time is 40~90s.

[0015] Preferably, in the silane coupling agent treatment solution, the mass ratio of KH-550 to KH-590 is 2:1, the treatment temperature is 30℃, the treatment time is 60min, the vacuum curing temperature is 110℃, and the curing time is 45min.

[0016] Preferably, the settling time for the copper ion pre-adsorption equalization treatment is 15~25 min.

[0017] Preferably, the temperature of the plating solution in multi-segment coupled pulse electroplating is controlled at 24~26℃, and the cathode oscillation frequency is 8 times / min.

[0018] Preferably, the positive pulse current density during the uniform nucleation pre-plating stage is 0.15~0.25A / dm², and the time is 6~9min.

[0019] Preferably, the forward pulse current density during the deep-hole mass transfer equalization stage is 0.4~0.6A / dm², the reverse pulse current is 1 / 4 of the forward current, and the duration is 25~35min.

[0020] Preferably, the forward pulse current density of the isotropic uniform filling stage is 1.0~1.5A / dm², the reverse pulse current is 1 / 3 of the forward current, and the time is 90~150min.

[0021] Preferably, the temperature of the first stage of the gradient annealing process is 130~140℃, the temperature of the second stage is 190~210℃, and the cooling rate is no higher than 3℃ / min.

[0022] A TGV glass substrate is prepared by the method described above.

[0023] The beneficial effects of this invention are as follows: The TGV deep-hole copper plating uniformity regulating electroplating solution of the present invention can reduce the internal stress of the plating layer, avoid the increase of plating layer brittleness, stabilize the performance of the plating solution, and is a uniformity-stress synergistic regulating electroplating solution.

[0024] This invention discloses a method for controlling the uniformity of TGV deep-hole copper plating, specifically developed to address the core needs of precise uniformity control and long-term internal stress optimization in high aspect ratio TGV deep-hole copper plating. It is applicable to core fields such as chiplet heterogeneous integration, 3D IC stacking, 6G RF device packaging, Mini / Micro LED display drivers, high-reliability automotive electronics packaging, and aerospace electronics packaging. It achieves synergistic control of uniformity and stress throughout the entire process from deposition to post-processing, without requiring large-scale modifications to existing mass production lines. It is fully compatible with mainstream TGV processing technologies and can achieve high consistency, high reliability, and low-cost large-scale mass production.

[0025] This invention, through a process of uniformity control and stress optimization throughout the entire process, can achieve 100% void-free and defect-free uniform filling of TGV deep holes with a depth-to-diameter ratio of 15:1. Its core performance indicators are significantly superior to existing mainstream technologies, as detailed below: ① Significantly improved coating uniformity: For TGV through-holes with a depth-to-diameter ratio of 10:1, the coating thickness difference between the orifice and the bottom of the orifice is ≤1.0μm, and the coating thickness dispersion coefficient of the entire orifice is ≤3%, which is more than 85% higher than the existing mainstream process; For TGV through-holes with a depth-to-diameter ratio of 15:1, the coating thickness difference between the orifice and the bottom of the orifice is ≤1.8μm, breaking through the upper limit of the depth-to-diameter ratio for uniformity control of existing technologies; ② Achieve ultra-low level stable control of internal stress: The residual tensile stress of the prepared copper coating is ≤30MPa, which is more than 75% lower than the existing mainstream process, and completely solves the reliability failure problems such as coating cracking, interface peeling, and glass substrate breakage. ③ Significantly optimized electrical performance: coating resistivity as low as 1.78×10^-8 Ω m, through-hole resistance dispersion coefficient ≤2%, insertion loss reduced by more than 35% at 10GHz high frequency, perfectly adapted to 6G RF and high-frequency high-speed packaging scenarios; ④ Long-term reliability meets high-level packaging standards: The product fully meets the JEDEC JESD22-A104 high-reliability packaging standard, with no failure after 1500 temperature cycles from -55℃ to 125℃, no abnormalities after 30 reflow soldering cycles at 260℃, and no blistering or peeling after 120 hours of PCT high-pressure boiling test. ⑤ Excellent mass production adaptability: The process is fully compatible with existing PCB / semiconductor electroplating production lines, requiring no additional vacuum equipment. The process time per batch is reduced by 20% compared to existing optimized processes, and production costs are reduced by more than 30%, enabling large-scale mass production.

[0026] Through a closed-loop process of "co-design of plating solution components - interface consistency pretreatment - precise control of multi-segment coupled pulse electroplating - long-term stress release of gradient annealing", the uniformity of high aspect ratio TGV deep hole copper plating is precisely controlled and the internal stress is stabilized at a low level. At the same time, it does not require large-scale modification of existing mass production lines, which greatly improves product yield and long-term reliability and adapts to the requirements of large-scale production.

[0027] The TGV glass substrate of this invention achieves the following effects: good coating uniformity, ultra-low and stable control of coating internal stress, low coating resistivity, long-term reliability reaching high-level packaging standards, and excellent mass production adaptability. Precise control of the uniformity and low-stress stability of the deep-hole copper plating enables high consistency, high reliability, and low-cost large-scale mass production. Detailed Implementation

[0028] To better understand the present invention, the following embodiments are provided for further detailed description of the present invention, but they should not be construed as limiting the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above-described invention are also considered to fall within the protection scope of the present invention.

[0029] A method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating, comprising the following steps: Example 1 This embodiment is designed for core scenarios such as 3D IC stacking and 6G RF packaging, and is adapted to TGV with a high aspect ratio of 10:1. The specific solution is as follows: 1. Uniformity-Stress Synergistic Regulation Special Electroplating Solution Formula (1L): 200g anhydrous copper sulfate, 70g concentrated sulfuric acid, 10g EDTA-2Na, 8g sodium citrate, 0.02g SPS, 0.01g MPS, 0.03g MBI, 0.02g PN, 1.0g PEG (molecular weight 8000), 0.3g modified nano SiO2, 0.8g sodium sulfite, deionized water to 1L; 2. TGV substrate parameters: Corning Eagle XG glass, thickness 200μm, via diameter 20μm, aspect ratio 10:1, via density 1200 / cm²; 3. Process steps: (1) Pretreatment: 55℃ alkaline degreasing ultrasonication for 12min → rinsing with flowing deionized water for 4min → etching with 25℃ BOE buffer etching solution for 60s → rinsing with flowing deionized water for 8min → drying with high-purity nitrogen → vacuum drying at 110℃ for 15min. (2) Oxygen plasma activation: cavity vacuum degree 20Pa, oxygen flow rate 30sccm, radio frequency power 200W, processing time 10min, and take it out immediately after processing; (3) Silane coupling agent interface modification: KH-550:KH-590=2:1, soaked at 30℃ for 60min, ultrasonically cleaned with anhydrous ethanol for 4min, dried with nitrogen and vacuum cured at 110℃ for 45min. (4) Copper ion pre-adsorption equalization treatment: let stand in the electroplating solution at room temperature for 20 min; (5) Multi-segment coupled pulse electroplating: electroplating solution temperature 25℃, cathode oscillation frequency 8 times / min, circulation filtration + microporous aeration and stirring; ① Uniform nucleation pre-plating stage: forward pulse current 0.2A / dm², pulse width 15ms, duty cycle 15%, time 8min; ② Deep hole mass transfer equalization stage: forward pulse current 0.5A / dm², width 30ms, duty cycle 25%; reverse pulse current 0.125A / dm², width 1.5ms, duty cycle 2%; time 30min; ③ Isotropic uniform filling stage: forward pulse current 1.2A / dm², width 20ms, duty cycle 20%; reverse pulse current 0.4A / dm², width 2.5ms, duty cycle 3%; time 120min; ④ Densification stress reduction stage: positive pulse current 0.4A / dm², width 40ms, duty cycle 35%, time 8min; (6) Gradient annealing: Under nitrogen atmosphere, hold at 130℃ for 25 min → hold at 200℃ for 45 min → cool to room temperature with furnace at a rate of 3℃ / min.

[0030] The test performance is as follows: ① Filling effect: 10:1 depth-to-diameter ratio through holes are 100% completely filled, with no voids, gaps, or protrusions; ② Coating uniformity: The coating thickness difference between the orifice and the bottom of the orifice is 0.8 μm, and the coating thickness variation coefficient throughout the orifice is 2.2%; ③ Internal stress: Residual tensile stress of the coating is 22 MPa; ④ Electrical properties: Coating resistivity 1.78×10^-8 Ω m, through-hole resistance dispersion factor 1.8%; ⑤ Reliability: After 1500 cycles of temperature cycling from -55℃ to 125℃, the resistance change rate is 2.5%, with no failures; after 30 reflow soldering cycles at 260℃, there are no abnormalities; after 120 hours of PCT testing, there are no blistering or peeling.

[0031] Example 2 This embodiment is designed for Mini / Micro LED display driver substrate scenarios and is compatible with large-area arrays and high-density 2:1 aspect ratio TGV. The difference between this embodiment and Embodiment 1 is: (1) TGV substrate parameters: Corning GG7 glass, thickness 100μm, through hole diameter 50μm, depth-to-diameter ratio 2:1, through hole density 5000 / cm²; (2) The time for the isotropic uniform filling stage is adjusted to 60 min; (3) The remaining electroplating solution formulations and process steps are completely consistent with those in Example 1; Performance test results: ① Filling effect: The through holes are 100% completely filled, with no voids or depressions, and the surface flatness is 0.5μm; ② Coating uniformity: The coating thickness difference between the orifice and the bottom of the orifice is 0.3 μm, and the coating thickness variation coefficient throughout the orifice is 1.2%; ③ Internal stress: Residual tensile stress of the coating is 18 MPa; ④ Electrical properties: Coating resistivity 1.77×10^-8 Ω m, through-hole resistance dispersion coefficient 0.9%; ⑤ Reliability: After 1500 cycles of temperature cycling from -55℃ to 125℃, the resistance change rate is 1.9%, with no failures; after 30 reflow soldering cycles at 260℃, there are no abnormalities.

[0032] Example 3 This embodiment is designed for high-reliability packaging scenarios in automotive and aerospace applications, and is compatible with TGV with an ultra-high aspect ratio of 15:1. The difference between this embodiment and Embodiment 1 is: (1) The modified nano-SiO2 added to the electroplating solution formula is 0.4 g / L, and the PEG added is 1.2 g / L; (2) TGV substrate parameters: Schott AF32 glass, thickness 300μm, through hole diameter 20μm, depth-to-diameter ratio 15:1, through hole density 800 / cm²; (3) The treatment time of silane coupling agent was adjusted to 90 min, and the pre-adsorption time of copper ions was adjusted to 30 min; (4) The time for the isotropic uniform filling stage is adjusted to 180 min; (5) The temperature of the second stage of gradient annealing is adjusted to 220℃ and the holding time is 60min; (6) All other parameters are completely consistent with those in Example 1; Performance test results: ① Filling effect: 15:1 depth-to-diameter ratio through holes are 100% completely filled, with no voids or gaps; ② Coating uniformity: The coating thickness difference between the orifice and the bottom of the orifice is 1.6 μm, and the coating thickness dispersion coefficient throughout the orifice is 2.8%; ③ Internal stress: Residual tensile stress of the coating is 28 MPa; ④ Electrical properties: Coating resistivity 1.79×10^-8 Ω m, through-hole resistance dispersion coefficient 1.9%; ⑤ Reliability: After 1500 temperature cycles from -55℃ to 125℃, the resistance change rate was 3.1%, with no failures; no abnormalities were observed after 120 hours of PCT testing.

[0033] Example 4 1. Uniformity-Stress Synergistic Regulation Special Electroplating Solution Formula (1L): 180g anhydrous copper sulfate, 60g concentrated sulfuric acid, 8g EDTA-2Na, 5g sodium citrate, 0.01g SPS, 0.005g MPS, 0.02g MBI, 0.01g PN, 0.8g PEG (molecular weight 8000), 0.2g modified nano SiO2, 0.5g sodium sulfite, deionized water to 1L.

[0034] 2. TGV substrate parameters: Corning Eagle XG glass, thickness 200μm, via diameter 20μm, aspect ratio 10:1, via density 1200 / cm²; anode contains 0.03% phosphorus copper spheres.

[0035] 3. Process steps: (1) Pretreatment: 50℃ alkaline degreasing ultrasonication for 10min → rinsing with flowing deionized water for 3min → etching with 20℃ BOE buffer etching solution for 30s → rinsing with flowing deionized water for 5min → drying with high-purity nitrogen → vacuum drying at 100℃ for 10min. (2) Oxygen plasma activation: cavity vacuum degree 10Pa, oxygen flow rate 20sccm, radio frequency power 100W, processing time 5min, and take it out immediately after processing; (3) Silane coupling agent interface modification: KH-550:KH-590=1:1, soaked at 25℃ for 30min, ultrasonically cleaned with anhydrous ethanol for 3min, dried with nitrogen and vacuum cured at 100℃ for 30min. (4) Copper ion pre-adsorption equalization treatment: let stand in the electroplating solution at room temperature for 10 min; (5) Multi-segment coupled pulse electroplating: electroplating solution temperature 22℃, cathode oscillation frequency 5 times / min, circulation filtration + microporous aeration and stirring; ① Uniform nucleation pre-plating stage: forward pulse current 0.1A / dm², pulse width 10ms, duty cycle 10%, time 5min; ② Deep hole mass transfer equalization stage: forward pulse current 0.3A / dm², width 20ms, duty cycle 20%; reverse pulse current is 1 / 4 of the forward pulse current, width 1ms, duty cycle 1%, time 20min; ③ Isotropic uniform filling stage: forward pulse current 0.8A / dm², width 10ms, duty cycle 10%; reverse pulse current is 1 / 3 of the forward pulse current, width 2ms, duty cycle 2%, time 120min; ④ Densification stress reduction stage: positive pulse current 0.3A / dm², width 30ms, duty cycle 30%, time 5min; (6) Gradient annealing: Under nitrogen atmosphere, hold at 120℃ for 20 min → hold at 180℃ for 30 min → cool to room temperature with furnace at a rate of 5℃ / min.

[0036] Performance test results: ① Filling effect: 10:1 depth-to-diameter ratio through holes are 100% completely filled, with no voids, gaps, or protrusions; ② Coating uniformity: The coating thickness difference between the orifice and the bottom of the orifice is 0.9 μm, and the coating thickness dispersion coefficient throughout the orifice is 2.7%; ③ Internal stress: Residual tensile stress of the coating is 26 MPa; ④ Electrical properties: Coating resistivity 1.79×10^-8 Ω m, through-hole resistance dispersion coefficient 2.1%; ⑤ Reliability: After 1500 temperature cycles from -55℃ to 125℃, the resistance change rate is 2.9%, with no failures; after 30 reflow soldering cycles at 260℃, there are no abnormalities; after 120 hours of PCT testing, there are no blistering or peeling.

[0037] Example 5 1. Uniformity-Stress Synergistic Regulation Special Electroplating Solution Formula (1L): 220g anhydrous copper sulfate, 80g concentrated sulfuric acid, 12g EDTA-2Na, 10g sodium citrate, 0.03g SPS, 0.015g MPS, 0.04g MBI, 0.03g PN, 1.2g PEG (molecular weight 8000), 0.5g modified nano SiO2, 1.0g sodium sulfite, deionized water to 1L.

[0038] 2. TGV substrate parameters: Corning Eagle XG glass, thickness 200μm, via diameter 20μm, aspect ratio 10:1, via density 1200 / cm²; anode contains 0.06% phosphorus copper spheres.

[0039] 3. Process steps: (1) Pretreatment: 60℃ alkaline degreasing ultrasonication for 15min → rinsing with flowing deionized water for 5min → etching with 25℃ BOE buffer etching solution for 120s → rinsing with flowing deionized water for 10min → drying with high-purity nitrogen → vacuum drying at 120℃ for 20min. (2) Oxygen plasma activation: cavity vacuum degree 30Pa, oxygen flow rate 50sccm, radio frequency power 300W, processing time 15min, and take it out immediately after processing; (3) Silane coupling agent interface modification: KH-550:KH-590=3:1, soaked at 40℃ for 90min, ultrasonically cleaned with anhydrous ethanol for 5min, dried with nitrogen and vacuum cured at 120℃ for 60min. (4) Copper ion pre-adsorption equalization treatment: let stand in the electroplating solution at room temperature for 30 min; (5) Multi-segment coupled pulse electroplating: electroplating solution temperature 28℃, cathode oscillation frequency 10 times / min, circulation filtration + microporous aeration and stirring; ① Uniform nucleation pre-plating stage: positive pulse current 0.3A / dm², pulse width 20ms, duty cycle 20%, time 10min; ② Deep hole mass transfer equalization stage: forward pulse current 0.8A / dm², width 40ms, duty cycle 30%; reverse pulse current is 1 / 3 of the forward pulse current, width 2ms, duty cycle 3%, time 40min; ③ Isotropic uniform filling stage: forward pulse current 2.0A / dm², width 30ms, duty cycle 25%; reverse pulse current is half of the forward pulse current, width 3ms, duty cycle 5%, time 120min; ④ Densification stress reduction stage: positive pulse current 0.5A / dm², width 50ms, duty cycle 40%, time 10min; (6) Gradient annealing: Under nitrogen atmosphere, hold at 150℃ for 30 min → hold at 220℃ for 60 min → cool to room temperature with furnace at a rate of 3℃ / min.

[0040] Performance test results: ① Filling effect: 10:1 depth-to-diameter ratio through holes are 100% completely filled, with no voids, gaps, or protrusions; ② Coating uniformity: The coating thickness difference between the orifice and the bottom of the orifice is 0.95 μm, and the coating thickness dispersion coefficient throughout the orifice is 2.8%; ③ Internal stress: Residual tensile stress of the coating is 27 MPa; ④ Electrical properties: Coating resistivity 1.78×10^-8 Ω m, through-hole resistance dispersion coefficient 2.0%; ⑤ Reliability: After 1500 cycles of temperature cycling from -55℃ to 125℃, the resistance change rate is 3.0%, with no failures; after 30 reflow soldering cycles at 260℃, there are no abnormalities; after 120 hours of PCT testing, there are no blistering or peeling.

[0041] Example 6 1. Uniformity-Stress Synergistic Regulation Special Electroplating Solution Formula (1L): 220g anhydrous copper sulfate, 70g concentrated sulfuric acid, 12g EDTA-2Na, 5g sodium citrate, 0.01g SPS, 0.005g MPS, 0.04g MBI, 0.03g PN, 1.0g PEG (molecular weight 8000), 0.2g modified nano SiO2, 1.0g sodium sulfite, deionized water to 1L.

[0042] 2. TGV substrate parameters: Corning Eagle XG glass, thickness 200μm, via diameter 20μm, aspect ratio 10:1, via density 1200 / cm²; anode contains 0.045% phosphorus copper spheres.

[0043] 3. Process steps: (1) Pretreatment: 55℃ alkaline degreasing ultrasonication for 12min → rinsing with flowing deionized water for 4min → etching with 22℃ BOE buffer etching solution for 90s → rinsing with flowing deionized water for 8min → drying with high-purity nitrogen → vacuum drying at 110℃ for 15min. (2) Oxygen plasma activation: cavity vacuum degree 20Pa, oxygen flow rate 40sccm, radio frequency power 150W, processing time 8min, and take it out immediately after processing; (3) Silane coupling agent interface modification: KH-550:KH-590=2:1, soaked at 35℃ for 60min, ultrasonically cleaned with anhydrous ethanol for 4min, dried with nitrogen and vacuum cured at 110℃ for 45min. (4) Copper ion pre-adsorption equalization treatment: let stand in the electroplating solution at room temperature for 15 min; (5) Multi-segment coupled pulse electroplating: electroplating solution temperature 25℃, cathode oscillation frequency 7 times / min, circulation filtration + microporous aeration and stirring; ① Uniform nucleation pre-plating stage: forward pulse current 0.25A / dm², pulse width 15ms, duty cycle 15%, time 7min; ② Deep hole mass transfer equalization stage: forward pulse current 0.6A / dm², width 35ms, duty cycle 25%; reverse pulse current is 1 / 3 of the forward pulse current, width 1.5ms, duty cycle 2%, time 35min; ③ Isotropic uniform filling stage: forward pulse current 1.5A / dm², width 25ms, duty cycle 20%; reverse pulse current is 1 / 3 of the forward pulse current, width 2.5ms, duty cycle 4%, time 120min; ④ Densification stress reduction stage: positive pulse current 0.35A / dm², width 35ms, duty cycle 35%, time 7min; (6) Gradient annealing: Under nitrogen atmosphere, hold at 140℃ for 25 min → hold at 200℃ for 50 min → cool to room temperature with furnace at a rate of 4℃ / min.

[0044] Performance test results: ① Filling effect: 10:1 depth-to-diameter ratio through holes are 100% completely filled, with no voids, gaps, or protrusions; ② Coating uniformity: The coating thickness difference between the orifice and the bottom of the orifice is 0.85 μm, and the coating thickness dispersion coefficient throughout the orifice is 2.5%; ③ Internal stress: Residual tensile stress of the coating is 24 MPa; ④ Electrical properties: Coating resistivity 1.78×10^-8 Ω m, through-hole resistance dispersion coefficient 1.9%; ⑤ Reliability: After 1500 temperature cycles from -55℃ to 125℃, the resistance change rate is 2.6%, with no failures; after 30 reflow soldering cycles at 260℃, there are no abnormalities; after 120 hours of PCT testing, there are no blistering or peeling.

[0045] Conclusion: This invention, through the synergistic regulation of uniformity and stress in a dedicated electroplating solution and the method for uniformity regulation and stress optimization of TGV deep-hole copper plating, can stably achieve precise uniformity regulation and long-term optimization of internal stress in TGV deep-hole copper plating under different aspect ratios and application scenarios. It significantly outperforms existing mainstream technologies in terms of plating uniformity, internal stress control, electrical performance, and long-term reliability. At the same time, it is fully compatible with existing mass production lines and has strong innovation and engineering application value.

[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A TGV deep-hole copper plating uniformity control electroplating solution, characterized in that... It includes the following components: Copper sulfate, sulfuric acid, disodium ethylenediaminetetraacetate, sodium citrate, disodium bis(3-sulfopropyl) disulfide, sodium 3-mercapto-1-propanesulfonate, 2-mercaptobenzimidazole, polyethyleneimine alkyl compounds, polyethylene glycol, modified nano silica, sodium sulfite, and deionized water.

2. The TGV deep-hole copper plating uniformity control electroplating solution as described in claim 1, characterized in that... The mass concentration percentages of each component are as follows: copper sulfate 180-220 g / L, sulfuric acid 60-80 g / L, disodium ethylenediaminetetraacetate 8-12 g / L, sodium citrate 5-10 g / L, disodium bis(3-sulfopropyl) disulfide 0.01-0.03 g / L, sodium 3-mercapto-1-propanesulfonate 0.005-0.015 g / L, 2-mercaptobenzimidazole 0.02-0.04 g / L, polyethyleneimine alkyl compound 0.01-0.03 g / L, polyethylene glycol 0.8-1.2 g / L, modified nano-silica 0.2-0.5 g / L, sodium sulfite 0.5-1.0 g / L, and the balance being deionized water.

3. A method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating, characterized in that, Includes the following steps: Step 1, Pretreatment of TGV glass substrate: The glass substrate with prepared through holes is subjected to alkaline degreasing, water washing and BOE buffer micro-roughening in sequence, and then water washing, blowing and vacuum drying. Step 2, Plasma interface activation treatment: The glass substrate treated in Step 1 is activated by oxygen plasma interface. Step 3, silane coupling agent interface modification: The activated TGV glass substrate is immersed in a silane coupling agent treatment solution for modification, and then cleaned, dried and vacuum cured. Step 4, copper ion pre-adsorption treatment: The modified TGV glass substrate is left to stand in the electroplating solution as described in claim 1 or 2 without electricity. Step 5, Coordinated regulation of uniformity and stress in multi-segment coupled pulse electroplating: Using the TGV glass substrate obtained in step 4 as the cathode and the phosphorus copper ball as the anode, deep hole copper plating is completed in the electroplating solution as described in claim 1 or 2 using four-segment coupled pulse electroplating. Step 6, gradient annealing: After electroplating, clean and dry, then perform three-stage gradient annealing in a nitrogen atmosphere.

4. The method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating as described in claim 3, characterized in that: Step 1, Pretreatment of TGV glass substrate: The glass substrate with prepared through holes is subjected to alkaline degreasing at a temperature of 50-60℃ for 10-15 min, followed by rinsing with flowing deionized water for 3-5 min, and then micro-roughening with BOE buffer etching solution at a temperature of 20-25℃ for 30-120 s. The volume ratio of hydrofluoric acid, ammonium fluoride, and water in the BOE buffer etching solution is 1:5:

1. The substrate is then rinsed with flowing deionized water for 5-10 min, dried with high-purity nitrogen, and vacuum dried at 100-120℃ for 10-20 min.

5. The method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating as described in claim 3, characterized in that: Step 2, Plasma Interface Activation Treatment: Place the TGV glass substrate treated in Step 1 into the plasma equipment cavity for oxygen plasma activation: cavity vacuum degree 10~30Pa, oxygen flow rate 20~50sccm, radio frequency power 100~300W, treatment time 5~15min; remove immediately after treatment and proceed to the next step.

6. The method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating as described in claim 3, characterized in that: Step 3, Silane Coupling Agent Interface Modification: The activated TGV glass substrate is immediately immersed in the silane coupling agent treatment solution at a temperature of 25~40℃ for 30~90 min. After treatment, it is ultrasonically cleaned with anhydrous ethanol for 3~5 min, dried with nitrogen, and vacuum cured at 100~120℃ for 30~60 min. The silane coupling agent treatment solution is a mixture of silane coupling agent, anhydrous ethanol, and deionized water, with a volume ratio of 5:90:

5. The silane coupling agent is a mixture of KH-550 and KH-590, with a mass ratio of 1~3:

1.

7. The method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating as described in claim 3, characterized in that: Step 4, Copper ion pre-adsorption equalization treatment: Immerse the modified TGV glass substrate in the electroplating solution and let it stand for 10-30 minutes at room temperature without power. Step 5, Multi-segment coupled pulse electroplating uniformity and stress synergistic control: Using the TGV glass substrate obtained in Step 4 as the cathode and phosphorus-containing copper balls as the anode, with a phosphorus content of 0.03-0.06% by mass, place it in the electroplating solution at a temperature of 22-28℃, using circulating filtration and microporous aeration stirring, with a cathode oscillation frequency of 5-10 times / min, and employing a four-segment coupled pulse electroplating method. Step 6, Gradient annealing treatment: After electroplating, rinse with flowing deionized water for 10-15 minutes and dry with high-purity nitrogen. Placed in a nitrogen atmosphere oven, it is annealed using a three-stage gradient process.

8. The method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating as described in claim 3, characterized in that: The aperture of the glass substrate with the through-holes is 10~100μm, and the aspect ratio is 2:1~15:

1. The specific method of the four-segment coupled pulse electroplating in step five is as follows: Uniform nucleation pre-plating stage: forward pulse current 0.1~0.3A / dm², pulse width 10~20ms, duty cycle 10~20%, time 5~10min; Deep hole mass transfer equalization stage: forward pulse current 0.3~0.8A / dm², width 20~40ms, duty cycle 20~30%; reverse pulse current is 1 / 4~1 / 3 of the forward pulse current, width 1~2ms, duty cycle 1~3%, time 20~40min; Isotropic uniform filling stage: forward pulse current 0.8~2.0A / dm², width 10~30ms, duty cycle 10~25%; reverse pulse current is 1 / 3~1 / 2 of the forward pulse current, width 2~3ms, duty cycle 2~5%; time 60~180min; Densification stress reduction stage: positive pulse current 0.3~0.5A / dm², width 30~50ms, duty cycle 30~40%, time 5~10min.

9. The method for controlling the uniformity and optimizing the stress of TGV deep-hole copper plating as described in claim 3, characterized in that, The specific method for three-stage gradient annealing is as follows: First stage: Keep warm at 120~150℃ for 20~30 minutes; Second stage: Keep warm at 180~220℃ for 30~60 minutes; The third stage: the furnace is cooled to room temperature at a rate not exceeding 5°C / min.

10. A TGV glass substrate, characterized in that... Prepared by the method described in any one of claims 3-9.